Management Of The Promotion Of Kuliki Paragliding Karo As Sports Tourism Through Social Media - Bangun, Brema; Boby Helmi; Bangun, Arti Kurniaty (Journal Management of Sport, 2024)
This research aims to find out the use of social media carried out by the Kuliki Paragliding Karo in its tourism promotion. The researcher uses a qualitative research method with a phenomenological approach. The results of this study show that Kuliki Paragliding Karo uses Instagram as a promotional medium by uploading or uploading the latest photos and videos processed in an Instagramable manner so that those who see the post are interested in visiting the tourist attraction. The Instagram of Kuliki Paralayang Karo also reposted photos or videos of visitors who had visited the tourist attraction using the hashtag or hashtag Kuliki Paralading Karo. The Karo Paragliding Kuliki also made a highlight on their Instagram account so that those who see can find out in advance what is in the tourist attraction. The Kuliki Paragliding Karo promotes through social media Instagram is said to be successful with the increase in the number of visitors to the Kuliki Paragliding Karo tour and the increasing number of followers on the Kuliki Paragliding Karo Instagram account.